Faktor-Faktor Yang Mempengaruhi Kinerja Karyawan PT. Panca Prima Mining Samarinda - Heriyanto Heriyanto (Prodi Ilmu Administrasi Negara, 2017)
Factors - Factors Affecting Employee Performance PT. Panca Prima Mining Samarinda under the guidanceThe background of this research aspects of internal motivation and external motivation. The research data was obtained from the method of the results of respondents (questionnaire), as well as other research relefan with the object under study, in this case the secondary data from the company PT. Panca Prima Mining Samarinda. Analysis model used in this research is multiple linear regression analysis using SPSS 20.The hypothesis of this paper is the internal motivation and external motivation significant influence on employee performance. Internal motivation dominant influence on employee performance. This study aims to determine the effect of motivation on employee performance and determine the dominant variable affecting employee performance. The sampling technique in this study using the technique of the census population is all employees of PT. Panca Prima Mining Samarinda numbered 38 people. The analysis used in this research is multiple linear regression, hypothesis testing F test and t test. Based on the analysis of the author of the test results of the test F is F count> F table that is 11.995> 3.32 alpha 5% and strengthened Adjusted test of determination (R2)of0.373 means that internal motivation variable (X1) and external motivation (X2) significantly 37, 3% of the employee's performance variable (Y) is reinforced also by the significant level of 0.000 which means the internal motivation variable (X1) and external motivation (X2) have a significant influence simultaneously toward employee performance variable (Y). T test can be obtained t count> t table means variable employee performance (Y) has a significant influence on a significant level of 0.001 variable internal motivation (X1) and external motivation (X2) X1 t count> t table (3.705> 2.028) with a beta coefficient of 0,483 or 48.3% that were perceived to have a significant effect on internal motivation variable (X1) and external motivation (X2) the value of t count> t table (3.393> 2.028) and a significant level of 0.002 so that external motivation variable ( X2) has a significant influence on employee performance variable (Y) is reinforced with a beta coefficient of 0.0442, or 44.2%. Then the dominant variable influence on employee performance (Y) is the internal motivation (X1), variable internal motivation (X1) has the greatest value to the value of 0.483% and a significant level of 0.001. Then the hypothesis H1 and H2 hypothesis is accepted.